Validation of liquid biopsy for ESR1-mutation analysis in hormone-sensitive breast cancer: a pooled meta-analysis - Najim, Omar; Papadimitriou, Konstantinos; Broeckx, Glenn; Huizing, Manon; Tjalma, Wiebren (Frontiers in Oncology, 2023)
Several retrospective and prospective studies have shown that genomic alterations in Estrogen-receptor one (ESR1) could be characterized not only on tissue samples but also by sequencing circulating tumor DNA (ctDNA) in liquid biopsy. Therefore, liquid biopsy is considered to be a potential non-invasive surrogate to tissue biopsy. This meta-analysis is designed to validate the diagnostic application of liquid biopsy in testing ESR1-mutation. A Pooled meta-analysis of studies published between January 1 st , 2007 and March 1 st , 2021 was conducted regarding the methodologies used for ESR1 mutation analysis. Liquid biopsy is a valid, inexpensive and attractive non-invasive alternative to tumor biopsies for the identification of ESR1 mutations. Liquid biopsy for ESR 1 analysis would facilitate regular testing, allowing to monitor the sensitivity to ET and guide treatment strategy.